(untitled) (Revista Inclusiones, 2020)
At the present stage, in Russia, there is an urgent demand for the adaptation and modernization of the foreign language education to meet the steadily growing educational needs. The advancing status of foreign languages acquires special significance in the context of Russia’s inclusion in the world educational processes and global changes in social and economic development. In these conditions, the consistent implementation of the principle of the continuity in the educational process becomes especially relevant. The main direction of professional education is the development of a future technician’s personal and professional competencies. It requires new approaches to the organization and interdisciplinary integration of the content and technology of foreign language teaching.